An Effective Strategy of Introducing Chirality to Achieve Multifunctionality in Rare‐Earth Double Perovskite Ferroelectrics (Small Methods 9/2022). Issue 9 (19th September 2022) - Hu, Zhao‐Bo; Wang, Chang‐Feng; Sha, Tai‐Ting; Shi, Chao; Ye, Le; Ye, Heng‐Yun; Song, You; You, Yu‐Meng; Zhang, Yi
Abstract : Inside Front Cover In article number 2200421, Song, You, Zhang, and co‐workers found that the introduction of chirality is an efficient strategy for the targeted construction of multifunctionality, which simultaneously increased the possibility of obtaining multiaxial ferroelectricity and ferroelasticity, and effectively realized a large piezoelectric response. Moreover, chirality‐induced ferroelasticity would also achieve excellent magnetic or optical response driven by pressure.